1801 Mass. Acts 507-08 - (:unkn) unknown (My University, 1801)
An Act to Provide for the Storing and Safe Keeping of Gun Powder in the Town of Boston, and to Prevent Damage from the Same, ch. XX § 1: §1... That all Gun Powder imported and landed at the port of Boston, shall be brought to and lodged in the Powder House or Magazine in said town, and not elsewhere, on pain of confiscation of all Powder put or kept in any other house or place...
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER